2015
DOI: 10.1093/ntr/ntv218
|View full text |Cite
|
Sign up to set email alerts
|

Is Smoking a Predictor for Acute Mountain Sickness? Findings From a Meta-Analysis

Abstract: This is the first quantitative assessment of published studies on smoking and AMS, which shows smoking to be neither a risk, nor protective. Studies specifically focusing on smoking as a risk factor, should guide further research on this issue. Although all smokers should be strongly advised to quit, studies on risk factors for AMS focusing on other exposures could shed light on the full range of risks for AMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…To our knowledge, prior our study, only one meta-analysis explored the association between smoking and AMS and found that smoking was not significantly associated with AMS [22]. Different selection criteria may lead to different results; we used strict inclusion and exclusion criteria and obtained results that contrasted with those of the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, prior our study, only one meta-analysis explored the association between smoking and AMS and found that smoking was not significantly associated with AMS [22]. Different selection criteria may lead to different results; we used strict inclusion and exclusion criteria and obtained results that contrasted with those of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Vinnikov et al [22] performed a meta-analysis showing that smoking was not significantly associated with AMS. Different detailed method might get different conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise may aggravate acute high-altitude disease, but good physical fitness is not a protective factor. A meta-analysis by Vinnikov D showed that smoking may also be a risk factor 33 , but there was no significant difference in body mass index, age, or smoking and drinking status between the AMS group and the non-AMS group after high-altitude exposure, indicating that our sample homogeneity was relatively good. However, our current report indicated that the rs2070699 polymorphism within the EDN1 gene was an independent predictor of AMS, which was notable.…”
Section: Discussionmentioning
confidence: 75%
“… 17 However, Li et al , 21 and Vinnikov et al 22 found smoking to be a risk factor (RR=1.11 and HR=1.9, respectively) when studying occupational cohorts or climbers commuting to very high altitudes (above 4000 masl), results that were in line with those shown in the meta-analysis performed by Vinnikov et al (pooled OR=0.88, 95% CI 0.74 to 1.05). 23 …”
Section: Discussionmentioning
confidence: 99%
“… 12–15 Around 30% of the world’s population declare being active smokers, yet there is a notable lack of consensus regarding the relationship between smoking and AMS risk. A recent meta-analysis performed by Vinnikov et al 16 showed that there was no significant association between smoking and AMS, while another performed by Xu et al 17 found an association between smoking and AMS, the former being a protective factor. The smoking status of travellers is not routinely explored, potentially resulting in an incomplete or misguided approach in the pretravel advice and treatment they receive.…”
Section: Introductionmentioning
confidence: 97%